LSECs express functional NOD1 receptors: A role for NOD1 in LSEC maturation-induced T cell immunity in vitro. (September 2018) - Huang, Shunmei; Wu, Jun; Gao, Xiaoyan; Zou, Shi; Chen, Liwen; Yang, Xilang; Sun, Chan; Du, Yanqin; Zhu, Bin; Li, Jia; Yang, Xuecheng; Feng, Xuemei; et al.
Highlights: LSECs stimulated with MDP only can induce the upregulation of the co-inhibitory molecule PD-L1. DAP stimulation in vitro could promote LSEC maturation and activate HBV-specific T cell responses. T cells pre-primed by DAP-treated LSECs can inhibit HBV expression and replication in vivo. These results are of particular relevance for the regulation of the local innate immune response against HBV infections. Abstract: Liver sinusoidal endothelial cells (LSECs) are organ resident APCs capable of antigen presentation and subsequent tolerization of T cells under physiological conditions. In this study, we investigated whether LSEC pretreatment with NOD-like receptor (NLR) agonists can switch the cells from a tolerogenic to an immunogenic state and promote the development of T cell immunity. LSECs constitutively express NOD1, NOD2 and RIPK2. Stimulation of LSECs with DAP induced the activation of NF-κB and MAP kinases and upregulated the expression of chemokines (CXCL2/9, CCL2/7/8) and cytokines (IFN-γ, TNF-α and IL-2). Pretreatment of LSECs with DAP induced signiﬁcantly increased IFN-γ and IL-2-production by HBV-stimulated CD8 + T cells primed by DAP-treated LSECs. Consistently, a signiﬁcant reduction in the HBV DNA and HBsAg level occurred in mice receiving T cells primed by DAP-treated LSECs. MDP stimulation had no impact on LSECs or HBV-stimulated CD8 + T cells primed with MDP-treated LSECs except for the upregulation of PD-L1. DAP stimulation in vitro could promote LSEC maturation and activate HBV-specific T cell responses. These results are of particular relevance for the regulation of the local innate immune response against HBV infections.